THE ROLE OF RELIGIOUS COURT IN PREVENTION UNDERAGE MARRIAGE - Suadi, Amran (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
Indonesia is the second highest country in ASEAN in the prevalence of underage marriage after Cambodia and ranks 7th highest in the world for the absolute number of child brides. The tangent point of child marriage with the Religious Court enters through the case of marriage dispensation. As the authority of the Religious Courts, marriage dispensation is very dilemmatic and debatable because simultaneously the case is biased in value, between benefit, harmness, and community behavior. In sociology, society always changes and the difference is only in the nature or level of change. One of the fundamental aspects of the reflection of the Religious Court decisions that put forward efforts to prevent child marriages is to narrow the space for filing child marriage cases, examine the case more carefully by adding to the burden of proof, and the commitment of the parties to respond to the negative consequences of child marriages.